The Use of Spelling Method by Teachers in Reading and Writing Skills in Grade III Students - Vivi Anggraini; Honest Ummi Kaltsum (Contemporary Education and Community Engagement (CECE), 2026)
The objectives of this study are: (1) to describe the implementation of spelling method in reading and writing skills, (2) to describe the obstacles faced by teachers when using spelling method. This research uses descriptive qualitative method. Data collection techniques in this study consisted of 3 techniques, namely observation, interviews, and documentation. The results of the study explain that the spelling method can support the reading and writing skills of third grade students at SD Muhammadiyah Baitul Fallah. The successful process of using the spelling method is done gradually and routinely. In the application of the spelling method, students who have difficulty reading and writing have the opportunity to be guided by the teacher to read a sentence.